2017
DOI: 10.1111/ene.13474
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose transdermal nicotine in Parkinson's disease patients: a randomized, open‐label, blinded‐endpoint evaluation phase 2 study

Abstract: Background and purpose: Studies of the effects of nicotine on motor symptoms in Parkinson's disease (PD) brought out discordant results. The aim of the present study was to evaluate the efficacy and safety of high doses of transdermal nicotine on motor symptoms in PD. Methods: Forty PD patients were randomly assigned to a treated and untreated arm in an open-label study. Treated patients received increasing doses of nicotine to reach 90 mg/day by 11 weeks. This dosage was maintained for 28 weeks (W39) and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 24 publications
0
42
0
1
Order By: Relevance
“…Similarly, the porous delignified biofilm also exhibits slightly higher transparency than original wood slice (Figure b), due to the elimination of light absorption as the colored lignin was removed . Overall, the enhanced transparency makes our biofilms more cosmetically acceptable and also facilitates the observation of the skin condition such as the side effects (redness, dermatitis, etc) of feedback transdermal therapy of On‐skinE.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Similarly, the porous delignified biofilm also exhibits slightly higher transparency than original wood slice (Figure b), due to the elimination of light absorption as the colored lignin was removed . Overall, the enhanced transparency makes our biofilms more cosmetically acceptable and also facilitates the observation of the skin condition such as the side effects (redness, dermatitis, etc) of feedback transdermal therapy of On‐skinE.…”
Section: Resultsmentioning
confidence: 86%
“…Besides, human skin is also the largest therapeutic interface, the transdermal therapy is now one of the most useful ways to deliver a drug systemically for treating many diseases (such as emesia, Parkinson's disease, cancer, and diabetes mellitus). As seen in Figure g, our biofilms guide the directional flow of artificial sweat to trigger the lighting of LEDs with higher brightness than the original wood slice.…”
Section: Resultsmentioning
confidence: 99%
“…However, the occurrence of motor and postural complications (on average, in about 50% of patients after 3-5 years of treatment with this drug) hinder the functioning of a patient [20]. Posture-and motor-related disorders are accompanied by fluctuations in symptoms beyond motor sensory, autonomic and neuropsychiatric symptoms [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological observations showing a lower prevalence of Parkinson disease among smokers and caffeine drinkers has led to ongoing trials assessing nicotine (http://ClinicalTrials.gov identifier: NCT01560754) and caffeine (NCT01738178). While the data regarding disease modification from these trials have not yet been reported, both approaches have recently returned null results in relation to symptomatic benefits in Parkinson disease 6 , 7 . One other recently reported significant epidemiological observation highlighted that people who had been prescribed β‐agonist medications for asthma (eg, salbutamol) had lower rates of Parkinson disease, whereas increased rates of Parkinson disease were seen in patients taking a β‐blocker for hypertension (eg, propranolol) 8 .…”
Section: Targeting Treatmentsmentioning
confidence: 99%